Rising to the climate challenge - Smith, Murray, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2010)
Agriculture dominates economic activity within Australia's Murray-Darling Basin, with 41 percent of Australia's gross value of agricultural production generated from the basin and about two-thirds of this total production exported. Historically low rainfall has resulted in cutbacks in irrigator water allocations, urban water restrictions and reduced environmental flows. A key element of the Victorian Government's response to water scarcity has been to establish the Northern Victoria Irrigation Renewal Project (NVIRP) to plan, design and deliver a program of works that will modernize the Goulburn Murray Irrigation District (GMID). NVIRP is being funded by the State Government $600M AUS, urban water users $300M AUS, GMID water users $100M AUS and Australian Commonwealth Government $1 billion AUS. Modernization of the GMID irrigation distribution system will increase the standard of water delivery service to its customers, providing near-on-demand water delivery on-farm and a better managed delivery system for operator Goulburn-Murray Water. The project will reduce system losses (currently 780 to 870 GL per annum on average) and is anticipated to generate up to 425 GL of long term average annual water savings. This paper discusses the five core elements of the modernization program: 1. Automation of the main backbone channel system; 2. Farm to backbone connections; 3. Upgrading metering technologies; 4. Water savings; 5. Challenges of investing in modernizing irrigation assets and environmental flows simultaneously.
USCID water management conference
Northern Victoria irrigation renewal project
Presented at Upgrading technology and infrastructure in a finance-challenged economy: a USCID water management conference held on March 23-26, 2010 in Sacramento, California.